AHR and the Transcriptional Regulation of Type-17/22 ILC - Lee, Jacob S.; Cella, Marina; Colonna, Marco (Frontiers in Immunology, 2012)
Mucosal innate lymphoid cells (ILCs) are an emerging population of diverse and heterogeneous immune cells, all with the unique ability to mount a rapid response against invading pathogens. They are further divided into subsets based on their differing cell surface markers as well as in their functional specialization. In this review, we summarize recent reports describing the importance of the transcription factor aryl hydrocarbon receptor (AHR) in regulating the development of one of these subsets, the Type-17/22 ILCs, as well as in the organization of postnatal lymphoid structures. We discuss the mechanisms behind the AHR dependence for development in Type-17/22 ILCs as well as reviewing the proposed physiological ligands that are mediating this effect.